2002
DOI: 10.1002/arch.10065
|View full text |Cite
|
Sign up to set email alerts
|

Multitrophic interactions of the silverleaf whitefly, host plants, competing herbivores, and phytopathogens

Abstract: Our laboratory found that silverleaf whitefly (SLW; Bemisia argentifolii Bellows & Perring) feeding alters host plant physiology and chemistry. The SLW induces a number of host plant defenses, including pathogenesis-related (PR) protein accumulation (e.g., chitinases, beta-1,3-glucanases, peroxidases, chitosanases, etc.). Induction of the PR proteins by SLW feeding occurs in various plant species and varieties. The extent and type of induction is dependent on a number of factors that include host plant growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
84
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 51 publications
(70 reference statements)
6
84
0
Order By: Relevance
“…Like the differential greenhouse responses to GM, wounding, and JA, this also suggests that red oak POD responses may be unique to the attacking insect. While studies of POD in the context of herbivory have focused on total POD activity (e.g., Cipollini and Redman, 1999;Mayer et al, 2002;Roitto et al, 2003;Traw et al, 2003), the plant pathology literature provides many examples of pathogen-specific POD isoform activity or profiles (Kristensen et al, 1999;Kandan et al, 2002;Tognolli et al, 2002;Maksimov et al, 2003). In some cases, POD isoform function is based on hostplant substrate specificity and the production of specific defenses (CalderĂłn et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Like the differential greenhouse responses to GM, wounding, and JA, this also suggests that red oak POD responses may be unique to the attacking insect. While studies of POD in the context of herbivory have focused on total POD activity (e.g., Cipollini and Redman, 1999;Mayer et al, 2002;Roitto et al, 2003;Traw et al, 2003), the plant pathology literature provides many examples of pathogen-specific POD isoform activity or profiles (Kristensen et al, 1999;Kandan et al, 2002;Tognolli et al, 2002;Maksimov et al, 2003). In some cases, POD isoform function is based on hostplant substrate specificity and the production of specific defenses (CalderĂłn et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Wool & Hales (1996) reported that a previous infestation of cotton plants by Aphis gossypii decreased subsequent colonization by conspecific aphids. Another phloem-feeding insect, the silverleaf whitefly, Bemisia argentifolii , induced PR protein accumulation in collard and tomato plants, which negatively affected the colonization process of conspecific and heterospecific competitors (Mayer et al, 2002). Conversely, previous infestation by Myzus persicae (Sulzer) (Homoptera: Aphididae) carried out on three different peach cultivars led to an improvement of conspecific performance (Sauge et al, 2002(Sauge et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Host plants of phytophagous insects can significantly influence host susceptibility to entomopathogenic microorganisms in at least three different ways: (1) by affecting growth rates (SantiagoÁlvarez & Ortiz-Garcia 1992), (2) through dietary stress (Mayer et al 2002) or (3) through direct antimicrobial activity of the plant (Costa & Gaugler 1989b;Vega et al 1997;Lacey & Mercadier 1998;Inyang et al 1999a,b;Poprawski et al 2000a,b;Klingen et al 2002). In order to maximise the potentiality of B. bassiana as a component of integrated pest management of H. cunea, it is necessary to understand the effects of different environmental factors and agricultural practices on fungal efficacy.…”
mentioning
confidence: 99%